Near‐Infrared Tunable Surface Lattice Induced Transparency in a Plasmonic Metasurface. Issue 1 (28th November 2019) - Michaeli, Lior; Suchowski, Haim; Ellenbogen, Tal
Abstract: Collective coherent scattering at the surface of a plasmonic nanoparticle array is shown to induce tunable transparency windows at the localized plasmon band. Broadband phase measurements show that the enhanced transmission is accompanied by a large anomalous dispersion, which leads to a group delay as large as ∼ 8 fs within only 40 nm thick sample. This effect occurs over a wide tunable spectral range of ∼ 200 nm, and appears for two distinct counter‐propagating surface waves. The experimental observations are in good agreement with calculations based on coupled dipole approximation (CDA) and with finite‐difference time‐domain (FDTD) simulations. This study opens the door for implementation in the fields of sensing, displays, optical buffering, tunable filtering, and nonlinear optics. Abstract : Collective coherent scattering at the surface of a plasmonic nanoparticle array is experimentally and numerically shown to induce tunable transparency windows at the localized plasmon band. Broadband phase measurements show that the tunable enhanced transmission is accompanied by a large anomalous dispersion, which leads to a group delay as large as ∼ 8 fs within only 40 nm thick sample.